Auriculotherapy in pain treatment: a literature review (Research, Society and Development, 2022)
Introduction: Pain affects a large part of the population at some point in their lives. It is a subjective, complex, personal experience affected by affective-emotional variables. Auriculotherapy has been shown to be an integrative and complementary practice in health that is widely used and widespread for this dysfunction. Objective: The general objective of this article is to investigate the use of auriculotherapy in the treatment of pain. Methods: This is a systematic review carried out by searching Medline, Lilacs and Scielo databases, using the descriptors: auriculotherapy and pain; review and experimental articles published from 2012 to 2022 were selected. Results: Several studies in different areas of health have demonstrated the effectiveness of auriculotherapy in pain, with significant reductions in sensation and disability caused by the condition. Conclusion: There is a clear need for studies with a wider population to improve the technique and demonstrate the effectiveness of auriculotherapy, thus bringing benefits to the population, especially in reducing suffering and reducing the use of medicines.